Application of Novel Fulvic Acid-Coated Magnetite Nanoparticles for CO2−-Mediated Photoreduction of Cr(VI) - Arce, Valeria Beatriz (2018)
We here isolate fulvic acids from vermicompost to prepare and characterize novel fulvic acid-coated magnetite nanoparticles. UV-A irradiation of suspensions of the nanoparticles under different experimental conditions led to photo-reduction of Cr(VI). In anoxic conditions in the presence of formic acid, after 60 min of irradiation ca. 100% of Cr(VI) was reduced. Under these conditions, the carbon dioxide radical anions, CO2.-, mediated the photo-reduction of Cr(VI). However, the high reduction potential of Cr(VI) and the variety of reactive species generated upon UV-A irradiation make this nanomaterial also suitable for Cr(VI) photo-reduction also under aerobic conditions in the presence of formic acid or under anoxic conditions without the addition of formic acid. The possible photodegradation routes involved are discussed in detail.